Endomyocardial involvement in asymptomatic Latin American migrants with eosinophilia related to helminth infection: A pilot study. - Abiu Sempere; Fernando Salvador; Laia Milà; Guillem Casas; Xavier Durà-Miralles; Elena Sulleiro; Rosa Vila-Olives; Pau Bosch-Nicolau; Maria Luisa Aznar; Juan Espinosa-Pereiro; Begoña Treviño; Adrián Sánchez-Montalvá; et al. (Public Library of Science (PLoS), 2024)
Background Hypereosinophilic syndrome can produce cardiac involvement and endomyocardial fibrosis, which have a poor prognosis. However, there is limited information regarding cardiac involvement among migrants from Latin America with eosinophilia related to helminthiasis. Methods We conducted a pilot observational study where an echocardiography was performed on migrants from Latin America with both eosinophilia (>450 cells/μL) and a diagnosis of helminth infection, and on migrants from Latin America without eosinophilia or helminth infection. Microbiological techniques included a stool microscopic examination using the Ritchie's formalin-ether technique, and a specific serology to detect Strongyloides stercoralis antibodies. Results 37 participants were included, 20 with eosinophilia and 17 without eosinophilia. Twenty (54.1%) were men with a mean age of 41.3 (SD 14.3) years. Helminthic infections diagnosed in the group with eosinophilia were: 17 cases of S. stercoralis infection, 1 case of hookworm infection, and 2 cases of S. stercoralis and hookworm coinfection. Among participants with eosinophilia, echocardiographic findings revealed a greater right ventricle thickness (p = 0.001) and left atrial area and volume index (p = 0.003 and p = 0.004, respectively), while showing a lower left atrial strain (p = 0.006) and E-wave deceleration time (p = 0.008). An increase was shown in both posterior and anterior mitral leaflet thickness (p = 0.0014 and p = 0.004, respectively) when compared with participants without eosinophilia. Conclusions Migrants from Latin America with eosinophilia related to helminthic infections might present incipient echocardiographic alterations suggestive of early diastolic dysfunction, that could be related to eosinophilia-induced changes in the endomyocardium.